Perceived importance of the skills of a quality physical education teacher: Dutch PE students perspective - Nieminen, P. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: In today`s society Physical Education (PE) teachers are not only supposed to teach sport skills and keep children fit, but are supposed to educate them through sport, teach them positive attitudes about movement and fitness as well as knowledge about healthy living. Physical Education Teacher Education (PETE) tries to respond to the challenges by modifying the curriculum. Since PE practices may differ between institutes, even within a country, PE students might acquire different perceptions about the skills needed to be a quality PE teacher. The aim of the study was to investigate the perceived importance of skills to be a quality PE teacher among PE students, in three Dutch institutes: Zwolle, Groningen and Amsterdam, in the beginning of their university studies and at the end of their studies. Methods The subjects were 306 PE students from Zwolle (n=158), Groningen (n= 63), and Amsterdam (n = 85). Of these students 200 were junior students (1-2 yr) and 106 senior students (3-4 yr). The data were collected by a questionnaire which was originally in Finnish and then translated into Dutch. PE students were provided with a questionnaire assessing their perceptions of the importance of 45 skill aspects of a quality physical educator. The students responded to the items by rating the importance of each aspect on a 6-point Likert type scale (1= not at all important; 6= highly important). The original 45 skill items were combined into seven sum scores. The sum scores, based on means, were the following: pedagogical skills, interaction skills, skills to differentiate, assessment skills, skills to cooperate with the community at large, knowledge based skills and skills to combine music and movement. The reliabilities for the sum scores were .79, .78, .71, .64, .64, .80, and .82, respectively. Results / Discussion Pedagogical skills, interaction skills, skills to differentiate, and assessment skills were perceived as the most important skills of a quality PE teacher by the Dutch PE students. Skills to combine music and movement were seen as the least important. When comparing perceived importance of the skills between the three Dutch institutes, there were only a few differences. PE students in all three institutes agreed with the four most important skill categories. However, PE students in Groningen and Zwolle perceived the skills to cooperate with the community at large and knowledge based skills as more important than PE students in Amsterdam. The comparison of perceived importance of the skills of a quality PE teacher between junior and senior students showed some differences. In Amsterdam assessment skills were perceived more important by the senior students than by the junior students while in Groningen and in Zwolle knowledge based skills were rated higher by the senior students than by the junior students. Even though differences in the perceived importance of skills of a quality PE teacher were found between the Dutch institutes, the PE programs appeared to have little influence on the students` perceptions.